Efeitos do tratamento intramuscular por quinze dias com óleo de linhaça sobre a reatividade vascular em anéis de aorta de ratos - Nunes, Dieli Oliveira (2014)
Some vegetable oils are alternative sources of polyunsaturated fatty acid omega3, especially flaxseed oil, which have the highest concentration of omega-3 αlinolenic acid among vegetable seeds. Nutritional intervention, such as the increased ingestion of omega-3 fatty acids, has been considered as an effective strategy to prevent or reduce the risk factors of cardiovascular disease. Although flaxseed oil might have beneficial cardiovascular effects, the mechanism of vascular function is unclear. Therefore, we proposed to evaluate the effects of intramuscular treatment with flaxseed oil on vascular function in isolated rat aortic rings. Wistar rats were treated daily with flaxseed oil (0.1 mL, i.m.) or a control (0.1 mL mineral oil i.m.), for fifteen days. At the end of treatment, the rats were anesthetized and the plasma and serum samples were collected and stored at -80 °C until malondialdehyde and C-reactive protein analysis, respectively. Isolated aortic segments were used to evaluate the protein expression of cyclooxygenase2, superoxide anion (O2 .-) levels and vascular reactivity experiments. Flaxseed oil treatment (i.m.) increased the vasoconstrictor response to phenylephrine without changing acetylcholine or sodium nitroprusside vasodilators responses in aortic rings. Endothelium removal or incubation with L-NAME increased the response to phenylephrine in isolated aortic rings of controls and treated-rats, but these effects were similar in both groups. Incubation with indomethacin (10 mM), a nonselective cyclooxygenase inhibitor; NS 398 (1 mM), a cyclooxygenase-2 inhibitor; SQ 29.548 (1 mM), a TP receptor antagonist; furegrelate (1 mM), a thromboxane A2 synthase inhibitor; dexamethasone (1 mM), an inhibitor phospholipase A2; tiron (1 mM), a superoxide anion scavenger; and apocynin (10 mM), an NADPH oxidase inhibitor, partially reversed the flaxseed oil-induced increased reactivity to phenylephrine. In addition, this treatment increased the basal superoxide anion production and protein expression of cyclooxygenase-2 in the flaxseed oil group as compared to the control. However, no significant differences in plasma levels of malondialdehyde and C-reactive protein in serum. These findings suggest that changes in the contractile response to phenylephrine observed in animals exposed to flaxseed oil are associated with increased release of vasoconstrictor prostanoids derived from COX-2, especially TXA2, and increased reactive oxygen species, especially the superoxide anion via NADPH oxidase, resulting in oxidative stress. Thus, this study provides new insight into the effects of treatment (i.m.) with flaxseed oil on vascular function.